A Community-based Approach to Mainstream Human-Nature Interactions into Coastal Risk Governance: A case of Katrenikona, India - Dakey, Shruthi; Joshi, Shreya; Sukhwani, Vibhas; Deshkar, Sameer (Geographica Pannonica, 2022)
Coastal rural communities, being intricately associated with their ecological settings, are often highly vulnerable to climate change. Amongst the many approaches of reducing the coastal vulnerabilities and achieving climate change adaptation, a potential solution is to improve risk governance through integrated coastal zone management. The coastal risk governance signifies not only the actions of the state but also of other stakeholders, especially the local communities. Community-based approaches have also for long been advocated for effective adaptation and mitigation against climate adversities. While human-nature interactions can significantly influence disaster risks, this research makes an attempt to understand various decisions and choices that a coastal rural community makes based on such interactions to mitigate and manage the climate-induced adversities. Through structured interviews, this research first identifies the significant domains that reflect on the prevailing human-nature interactions, after which the choice modelling technique is utilized to comprehend the community priorities for better climate risk governance, with a specific focus on coastal rural settlements of Katrenikona (Andhra Pradesh, India). The application of this methodology resulted in the formulation of a baseline for local coastal governance, which can be useful for informing various levels within local governments. The baseline consists of an assessment of the different community resilience domains derived based on the prevailing interactions of local communities with their surrounding ecological elements and measured by indicators of local coastal governance. The concept and method for measuring coastal risk governance based on community preferences are potentially replicable, and it can help to track the progress towards longer-term coastal management and local climate adaptation goals. At the same time, it can be turned into a self-evaluation tool to assist the local governments in reflecting on pertinent pathways involving community actions for effectively managing various climate risks and ecological impacts.
Keywords: Coastal risk governance; human-nature interactions; community-based approach